The artefact assemblages (Scottish Historical and Archaeological Internet Reports, 2003)
This chapter presents specialist reports on artefact assemblages. Most of the coarse pottery came from Balelone, Baleshare and Hornish Point. It is acknowledged that many more well dated assemblages are needed to advance the pottery sequence for the West Coast Islands on a local and regional level. Lithics were mainly flint and quartz. The small size of the assemblages recovered and the types of contexts, cultural deposits and conflation deposits precludes any detailed discussion of the material. Geochemical analysis of pumice demonstrated that it can be correlated with dacitic pumice in Iceland, Ireland, Scotland and Norway. This material would have been collected either from contemporary or raised beach deposits and would have been used as an abrasive. Worked bone and antler included a noteworthy bone comb fragment from Hornish Point.